Features in scientific and technical cooperation in the field of non-conventional renewable energy - V. Babenko; V. Sidorov; Y. Koniaieva; L. Kysliuk (Global Journal of Environmental Science and Management)
This article discusses the prospects for the development of the implementation of scientific and technical cooperation. On the example of international cooperation between Ukraine and Chile, there are approaches to improving the procedure for developing cooperation priorities. The current state of these relations does not reflect real trends in the development of international economic relations in the vector of strengthening the scientific and technical component. Based on the analysis of analytical materials, one of the priority areas of the joint development of scientific and technical issues may be the use of non-traditional renewable energy technologies. Both in Ukraine and in Chile there are objective factors (natural, resource, socio-economic, environmental-technological) for their development. For Ukraine, it is interesting the experience of the scientific and production implementation of these technologies and the organizational and economic support of these priorities in the context of state and regional policy. All these aspects, including through the exchange of intellectual products, will make it possible to increase the effectiveness of support policies, the innovative susceptibility of subjects of production and business activities of Ukraine and the corresponding development of producers and consumers' motivation to non-conventional renewable energy technology.